Comparison of anterior decompression and fusion versus laminoplasty in the treatment of multilevel cervical ossification of the posterior longitudinal ligament: a systematic review and meta-analysis - Liu, Weijun (Ther Clin Risk Manag, 2016)
PURPOSE: A meta-analysis was conducted to evaluate the clinical outcomes, complications, reoperation rates, and late neurological deterioration between anterior decompression and fusion (ADF) and laminoplasty (LAMP) in the treatment of multilevel cervical ossification of the posterior longitudinal ligament (OPLL). METHODS: All related studies published up to August 2015 were acquired by searching PubMed and EMBASE. Exclusion criteria were case reports, revision surgeries, combined anterior and posterior surgeries, the other posterior approaches including laminectomy or laminectomy and instrumented fusion, non-English studies, and studies with quality assessment scores of <7. The main end points including Japanese Orthopedic Association (JOA) score, recovery rate of JOA, cervical lordosis, complication rate, reoperation rate, and late neurological deterioration were analyzed. All available data was analyzed using RevMan 5.2.0 and Stata 12.0. RESULTS: A total of seven studies were included in the meta-analysis. The mean surgical level of ADF was 3.1, and the mean preoperative occupation ratios of ADF and LAMP group were 55.9% and 51.9%, respectively. No statistical difference was observed with regard to preoperative occupation ratio and preoperative JOA score. Although LAMP group had a higher preoperative cervical lordosis than ADF group (P<0.05, weighted mean difference [WMD] =−5.73, 95% confidence interval [CI] =−9.67–−1.80), significantly decreased cervical lordosis was observed in LAMP group after operation. ADF group had higher postoperative JOA score (P<0.05, WMD =2.18, 95% CI =0.98–3.38) and neurological recovery rate (P<0.05, WMD =27.22, 95% CI =15.20–39.23). Furthermore, ADF group had a lower late neurological deterioration rate than the LAMP group (P<0.05, risk difference =0.16, 95% CI =0.04–0.73). The complication rates of both groups had no statistical difference. However, LAMP group had a significantly lower reoperation rate than ADF group. The reoperation rate of ADF group (20.5%) was almost six times that of LAMP group (3.5%). CONCLUSION: Our meta-analysis suggested that ADF was associated with better postoperative neurological function, neurological recovery rate, and less late neurological deterioration than LAMP in the treatment of multilevel cervical OPLL with a high mean occupation ratio. LAMP was associated with a decreased postoperative cervical lordosis, which might be a cause of late neurological deterioration. The complication rates of both groups showed no statistical difference. However, the reoperation rate was significantly higher in ADF group compared with LAMP group. Benefits and risks should be balanced when ADF or LAMP is selected.